2019
DOI: 10.3390/atmos10020078
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Sources of Water-Soluble Ions in PM2.5 in the Sichuan Basin, China

Abstract: To track the particulate pollution in Sichuan Basin, sample filters were collected in three urban sites. Characteristics of water-soluble inorganic ions (WSIIs) were explored and their sources were analyzed by principal component analysis (PCA). During 2012–2013, the PM2.5 concentrations were 86.7 ± 49.7 μg m−3 in Chengdu (CD), 78.6 ± 36.8 μg m−3 in Neijiang (NJ), and 71.7 ± 36.9 μg m−3 in Chongqing (CQ), respectively. WSIIs contributed about 50% to PM2.5, and 90% of them were secondary inorganic ions. NH4+ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A study performed in Heze, China 44 showed that ions mainly exist in the form of NH 4 NO 3 , NH 4 HSO 4 , and (NH 4 ) 2 SO 4 in winter and autumn, and the forms were more complex and diverse in spring and summer. Chen et al found that in Sichuan, China, the content of NH 4 + in most samples during spring was sufficient to neutralize SO 4 2 and NO 3 − to form (NH 4 ) 2 SO 4 and NH 4 NO 3 45 . A study in southeastern Italy 46 indicated there was a strong correlation between SO 4 2- and NH 4 + , with the ammonium salt in the form of ammonium sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…A study performed in Heze, China 44 showed that ions mainly exist in the form of NH 4 NO 3 , NH 4 HSO 4 , and (NH 4 ) 2 SO 4 in winter and autumn, and the forms were more complex and diverse in spring and summer. Chen et al found that in Sichuan, China, the content of NH 4 + in most samples during spring was sufficient to neutralize SO 4 2 and NO 3 − to form (NH 4 ) 2 SO 4 and NH 4 NO 3 45 . A study in southeastern Italy 46 indicated there was a strong correlation between SO 4 2- and NH 4 + , with the ammonium salt in the form of ammonium sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…The anion equivalence and cation equivalence ratio (AE/CE) can be measured to determine the acidity of PM 2.5 , which can be calculated using the equations below …”
Section: Results and Discussionmentioning
confidence: 99%
“…It is important to note that NO 2 − concentration was below the detection limit and was, therefore, not included in Equation (9). The scatter plot between CE and AE is presented in Figure 6b.…”
Section: General Characteristics Of Pm 25 Componentsmentioning
confidence: 99%
“…In particular, much effort has been devoted to the study of fine particles with an aerodynamic diameter less than 2.5 µm (PM 2.5 ) due to its adverse health effects. Along with rapid economic growth, PM 2.5 pollution events ('haze') have occurred frequently in China, and many studies have been carried out to elucidate the properties of PM 2.5 , especially in densely populated regions [4][5][6][7][8][9]. However, the chemical composition of PM 2.5 is highly complex, possibly containing a wide variety of components, including inorganic salts (nitrate, sulfate, and ammonium), trace metals, elemental carbon, and a large number of organic species.…”
Section: Introductionmentioning
confidence: 99%